El legado de Robert A. Brady: Orígenes antifascistas de la Economía Política de la Comunicación. (No disponible el texto completo del artículo) - Schiller, Dan (CIC. Cuadernos de Información y Comunicación, 2006)
During its formative period in the United States, the Political Economy of Communications was profoundly influenced be the teachings of the economist Robert A. Brady. Throughout the 1930s and 1940s, within the broader political context of of U.S. anti-fascism, Brady developed a potent analysis of emerging autoritharian economic and cultural practices. This framework was substantially carried over, and further developed, by the two pioneers of the Political Economy approach, Dallas W. Smythe and Herbet I. Schiller.